Making strange: Race science and ethnopsychiatric discourse - Manganyi, Chabani (PINS-Psychology in Society, 2018)
The inscription of racial difference – or what I refer to as the discursive practice of making strange - is to be found in many of the most revered texts of Western modernity. The irreducible recognition and constitution of otherness is evident in Hegel, Marx and indeed Freud, whose preoccupation with the primal horde, primitive man, the cannibalistic savage and the unruly child show the extent to which psychoanalysis, and thereby early psychology, has been a crucial link in the chain of colonial discourse. The discursive practice of making strange is evident in ethnopsychiatry – particularly in the colonial discourse on Africa and Africans – and it continues through the history of psychology where the inscription of blackness is perhaps best epitomized in notions of intellectual inferiority or – turning to the Southern African context – in the domain of “African psychological research”.